Impact Of Discipline and Work Environment in Improving Job Performance - Yossi Hendriati; Indra Firdiyansyah; Dadi Akhmad Perdana; Kiki Wulandari (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
This study for to know the cultural influence work to officer motivation of at office of Mayor Batam, to know the professionalism influence to officer motivation of at office of mayor Batam and to know the cultural influence work and proffesionalism by together to officer motivation of at office of Mayor Batam. Result of research, result of calculation obtained by cultural value t hitung variable work bigger that t tabel. There by hence Ho refused and is Ha accepted. Matter of this means that there are influence which significant and positive among/between culture work to officer motivation of at office of mayor batam. Is meaning, more and more the cultural goodness work, hence will more and more the goodness also motivate the officer of at office of Mayor Batam and constructivelly computer processing of pursuant to calculation SPSS obtained by value F Hitung of bigger than F tabel, clear so that Ho refused and is Ha accepted. This matter indicate that by together culture work and professionalism can improve the officer motivation of at office of mayor batam. This indicate that there are very influence of significant of among/between culture work and profeesionalism to officer motivation of at office of mayor batam.